THE ROLE OF CCU IN ENGLISH CLASSROOM IN INDONESIA - Hikmatulloh Hikmatulloh; Ahmad Syafi’i (Universitas Sarjanawiyata Tamansiswa, 2020)
Language cannot be separated from culture, so if we teach a language, we also need to correlate it with culture. It implies that to teach language means to also teach the culture. Since English now belongs to the world asÂ lingua franca, used by different nationalities, the number of students who learn English increases around the world. The increase of students who learn English in countries with various ethnicities makes multicultural education in the 21st century. This phenomenon happens especially in a diverse country such as Indonesia that has thousands of ethnicities, languages, religions, and cultures. Language and religious diversity are also increasing among the nationâ€™s student population (Dilg, 2003). ln an EFL country such as Indonesia, teaching cross-cultural understanding (CCU) is extremely needed in order to understand the language taught. This paper will discuss the use of CCU in English classrooms, especially in Indonesia.